ANALISIS PENGARUH PDB, KURS RUPIAH TERHADAP USD, TINGKAT INFLASI, BI RATE, DAN IHSG TERHADAP INDEKS HARGA SAHAM SEKTOR KEUANGAN (PERIODE PENGAMATAN TAHUN 2006-2011) - , Irani Ruth Julita Sinaga ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Many factors can influence the movement of the stock price index, among others, changes in interest rates of the central bank, global economic conditions, the level of world energy prices, political stability of a country, and so forth. Currently, the rate of economic growth in Indonesia continues to increase. It can make the economic potential of Indonesia as one of the most attractive investment destinations in the world. The financial sector is one of many sectors that many investors interested in investing in the stock market and one sector that continues to be a phenomenon in the IDX given sector are influenced by macroeconomic factors and the number of companies that grow and move in the financial sector. This study aimed to analyze the influence of economic growth proxied by GDP (Gross Domestic Product), the exchange rate against the U.S. dollar, the inflation rate, the BI rate, and JCI (Jakarta Composite Index) for the financial sector stock indices. This study includes data analysis observations by year 2006-2011. The types of data used in this research is secondary data monthly, except GDP using quarterly data. The method of analysis is an econometric modeling approach to time series data. The model used in accordance with the test results stationarity of each variable. Model cointegration and ECM / VECM (error correction model / vector error correction model) is used if at least one of the variables in an equation are not stationary. The results indicates that the stock price index, the financial sector is not significantly influenced by the exchange rate against the U.S. dollar, the central bank rate, inflation, GDP, and JCI. Meanwhile, BIRATE, EXCHANGE, and INFLATION are variables that are sensitive enough influenced by changes in other variables. This supports the hypothesis formed, but did not support previous research that indicates that the stock price index of the financial sector is affected significantly by the financial variables, such as the dollar exchange rate against the U.S. dollar.